Protective Effects of Cannabidiol against Seizures and Neuronal Death in a Rat Model of Mesial Temporal Lobe Epilepsy - Do Val-da Silva, Raquel A.; Peixoto-Santos, Jose E.; Kandratavicius, Ludmyla; De Ross, Jana B.; Esteves, Ingrid; De Martinis, Bruno S.; Alves, Marcela N. R.; Scandiuzzi, Renata C.; Hallak, Jaime E. C.; Zuardi, Antonio W.; Crippa, Jose A.; Leite, Joao P. (Frontiers in Pharmacology, 2017)
The present study reports the behavioral, electrophysiological, and neuropathological effects of cannabidiol (CBD), a major non-psychotropic constituent of Cannabis sativa, in the intrahippocampal pilocarpine-induced status epilepticus (SE) rat model. CBD was administered before pilocarpine-induced SE (group SE+CBDp) or before and after SE (group SE+CBDt), and compared to rats submitted only to SE (SE group), CBD, or vehicle (VH group). Groups were evaluated during SE (behavioral and electrophysiological analysis), as well as at days one and three post-SE (exploratory activity, electrophysiological analysis, neuron density, and neuron degeneration). Compared to SE group, SE+CBD groups (SE+CBDp and SE+CBDt) had increased SE latency, diminished SE severity, increased contralateral after discharges latency and decreased relative powers in delta (0.5-4 Hz) and theta (4-10 Hz) bands. Only SE+CBDp had increased vertical exploratory activity one-day post SE and decreased contralateral relative power in delta three days after SE, when compared to SE group. SE+CBD groups also showed decreased neurodegeneration in the hilus and CA3, and higher neuron density in granule cell layer, hilus, CA3, and CA1, when compared to SE group. Our findings demonstrate anticonvulsant and neuroprotective effects of CBD preventive treatment in the intrahippocampal pilocarpine epilepsy model, either as single or multiple administrations, reinforcing the potential role of CBD in the treatment of epileptic disorders.